2006
DOI: 10.1186/1472-6939-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practice of healthcare ethics and law among doctors and nurses in Barbados

Abstract: BackgroundThe aim of the study is to assess the knowledge, attitudes and practices among healthcare professionals in Barbados in relation to healthcare ethics and law in an attempt to assist in guiding their professional conduct and aid in curriculum development.MethodsA self-administered structured questionnaire about knowledge of healthcare ethics, law and the role of an Ethics Committee in the healthcare system was devised, tested and distributed to all levels of staff at the Queen Elizabeth Hospital in Bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
178
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(220 citation statements)
references
References 16 publications
30
178
3
2
Order By: Relevance
“…The present study also concludes that majority (90.6%) of the nurses perceived that knowledge of ethics to nurses is very important. This finding is similar to the findings of other studies (Iglesias & Vallejo, 2014;Hariharan et al, 2006). This study also finds that the major source of knowledge about ethics is reported as nursing curriculum 79.2 percent which is similar with the finding of Mohajjel-Aghdam et al (2013).…”
Section: Discussionsupporting
confidence: 83%
“…The present study also concludes that majority (90.6%) of the nurses perceived that knowledge of ethics to nurses is very important. This finding is similar to the findings of other studies (Iglesias & Vallejo, 2014;Hariharan et al, 2006). This study also finds that the major source of knowledge about ethics is reported as nursing curriculum 79.2 percent which is similar with the finding of Mohajjel-Aghdam et al (2013).…”
Section: Discussionsupporting
confidence: 83%
“…The findings of this study indicated gaps in the knowledge about the practical aspects of health care ethics among nurses and physicians, which they encounter in day-to-day practice in their workplace and recommended that practical education in ethics, could assist in bridging the gap in ethical approaches among different levels of healthcare staff. Similarly, in a study of Hariharan et al, [15] the researchers found that physicians had a stronger opinion than nurses regarding the practice of ethical comportment such as adherence to patients' wishes, consent for procedures, confidentiality and treating non-compliant patients and the study recommended that practical education in ethical comportment, particularly in a multidisciplinary settings, could assist in bridging the gap in ethical approaches between physicians and nurses. [15] In the current study, students were trained to view patients' problems from all aspects as physical needs, psychological needs, etc.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, in a study of Hariharan et al, [15] the researchers found that physicians had a stronger opinion than nurses regarding the practice of ethical comportment such as adherence to patients' wishes, consent for procedures, confidentiality and treating non-compliant patients and the study recommended that practical education in ethical comportment, particularly in a multidisciplinary settings, could assist in bridging the gap in ethical approaches between physicians and nurses. [15] In the current study, students were trained to view patients' problems from all aspects as physical needs, psychological needs, etc. In addition, they were trained to analyze patients' problems from the ethic of caring.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations